2021
DOI: 10.1161/jaha.120.018176
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women After Arterial Switch Operation for Transposition of the Great Arteries: Results From ROPAC (Registry of Pregnancy and Cardiac Disease) of the European Society of Cardiology EURObservational Research Programme

Abstract: Background In the past 3 decades, the arterial switch procedure has replaced the atrial switch procedure as treatment of choice for transposition of the great arteries. Although survival is superior after the arterial switch procedure, data on pregnancy outcomes are scarce and transposition of the great arteries after arterial switch is not yet included in the modified World Health Organization classification of maternal cardiovascular risk. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Our review identified 120 pregnancies in 86 women with TGA and a history of ASO (Table 5 ). 23 , 24 , 25 , 26 Prior palliative procedures were reported in about a third of the patients, including atrial balloon septostomy, PA banding, ventricular septal defect closure, PA interventions, aortic coarctation repair, and LeCompte procedure. Of the patients, 28% had interventions after the initial ASO, including a relief of RV outflow tract obstruction and PA stenosis, ascending aorta angioplasty, mitral valve repair and replacement, and RV to PA conduit.…”
Section: Resultsmentioning
confidence: 99%
“…Our review identified 120 pregnancies in 86 women with TGA and a history of ASO (Table 5 ). 23 , 24 , 25 , 26 Prior palliative procedures were reported in about a third of the patients, including atrial balloon septostomy, PA banding, ventricular septal defect closure, PA interventions, aortic coarctation repair, and LeCompte procedure. Of the patients, 28% had interventions after the initial ASO, including a relief of RV outflow tract obstruction and PA stenosis, ascending aorta angioplasty, mitral valve repair and replacement, and RV to PA conduit.…”
Section: Resultsmentioning
confidence: 99%
“…Data from ROPAC have led to numerous publications outlining specific cardiac disease processes complicating pregnancy and, in turn, has helped clinicians better guide care for these patients. [5][6][7][8][9][10][11][12] Data from ROPAC demonstrate that although rates of maternal mortality and heart failure were high among women with particular types of CVD, 9% mortality with pulmonary arterial hypertension and 11% rate of heart failure in the entire study population overall, most patients with CVD did well, suggesting that safe pregnancy can be achieved with proper care. 13 ROPAC also highlights the high rate of obstetric and fetal complications in pregnancies complicated by CVD, at 17% and 21%, respectively.…”
Section: Planning For Delivery Framework Who: the Patient And Pregnan...mentioning
confidence: 99%
“…El registro europeo ROPAC ha comunicado los datos de las mujeres embarazadas con TGA 24 , 25 . El registro confirma que las mujeres intervenidas con técnica de switch arterial presentan un bajo riesgo de complicaciones (clase II de la OMSm).…”
Section: Embarazo Y Cardiopatíaunclassified